Loss of the Cochlear Amplifier Prestin Reduces Temporal Processing Efficacy in the Central Auditory System - Walton, Joseph P.; Dziorny, Adam C.; Vasilyeva, Olga N.; Luebke, Anne E. (Frontiers in Cellular Neuroscience, 2018)
Active mechanical amplification of sound occurs in cochlear outer hair cells (OHCs) that change their length with oscillations of their membrane potential. Such length changes are the proposed cellular source of the cochlear amplifier, and prestin is the motor protein responsible for OHC electromotility. Previous findings have shown that mice lacking prestin displayed a loss of OHC electromotility, subsequent loss of distortion-product otoacoustic emissions, and a 40-60 dB increase hearing thresholds. In this study we were interested in studying the functional consequences of the complete loss of cochlear amplification on neural coding of frequency selectivity, tuning, and temporal processing in the auditory midbrain. We recorded near-field auditory evoked potentials and multi-unit activity from the inferior colliculus of prestin (-/-) null and prestin (+/+) wildtype control mice and determined frequency response areas, tuning sharpness, and gap detection to tone bursts and silent gaps embedded in broadband noise. We were interested in determining if the moderate to severe sensorineural hearing loss associated with the loss of motor protein prestin would also impair auditory midbrain temporal-processing measures, or if compensatory mechanisms within the brainstem could compensate for the loss of prestin. In prestin knockout mice we observed that there are severe impairments in midbrain tuning, thresholds, excitatory drive, and gap detection suggesting that brainstem and midbrain processing could not overcome the auditory processing deficits afforded by the loss of OHC electromotility mediated by the prestin protein.